1994
DOI: 10.1097/00006250-199404000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy in the United States, 1988-1990

Abstract: Two-thirds of all hysterectomies for noncancerous conditions were performed for uterine leiomyoma or endometriosis--conditions that are most common before the age of menopause. Future assessments of the appropriateness of hysterectomy will require better understanding of these disorders. Continued monitoring of hysterectomy rates is critical to understanding the appropriate use of hysterectomy, alternative therapies for uterine disorders, and future trends in women's health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
284
0
29

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 623 publications
(322 citation statements)
references
References 0 publications
7
284
0
29
Order By: Relevance
“…An increase with age in the prevalence of fibroids during the reproductive years has been demonstrated by several epidemiologic studies (Marshall et al 1997;Ross et al 1986;Velebil et al 1995;Wilcox et al 1994). Studies that define cases by pathologic diagnosis, thus restricting cases to those having surgery (Ross et al 1986), have shown a rapid increase in fibroid diagnoses among women in their forties.…”
Section: Agementioning
confidence: 98%
See 1 more Smart Citation
“…An increase with age in the prevalence of fibroids during the reproductive years has been demonstrated by several epidemiologic studies (Marshall et al 1997;Ross et al 1986;Velebil et al 1995;Wilcox et al 1994). Studies that define cases by pathologic diagnosis, thus restricting cases to those having surgery (Ross et al 1986), have shown a rapid increase in fibroid diagnoses among women in their forties.…”
Section: Agementioning
confidence: 98%
“…The clinical effects of these tumors are related to their local mass effect, resulting in pressure upon adjacent organs, excessive uterine bleeding, or problems related to pregnancy, including infertility and repetitive pregnancy loss (Haney 2000). As a consequence of these local pressure effects and bleeding, uterine fibroids rank as the major reason for hysterectomy in the United States, accounting for approximately one-third of all hysterectomies (Wilcox et al 1994), or about 200,000 hysterectomies per year (Gambone et al 1990). …”
mentioning
confidence: 99%
“…5,6 Because of the benign nature of the disease, supracervical or subtotal hysterectomy through a laparoscopic or open approach has been introduced. The supracervical hysterectomy removes only the uterus and leaves the cervix with the intention of preserving sexual, urinary, and bowel function.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is estimated that 20 -30% of women over the age of 30 will develop a leiomyoma. 1,3 Approximately half of the cases exhibit cytogenetic abnormalities. The most frequent genetic alterations are translocations involving the 12q15 region and deletions within the large arm of chromosome 7.…”
mentioning
confidence: 99%